Semi-insulating gallium arsenide single crystal and its manufacturing method and growth apparatus

By employing a VGF method with graphite and quartz in separate temperature zones and pretreating the graphite, the method addresses the issue of non-uniform carbon doping in GaAs crystals, achieving improved resistivity and mobility for enhanced commercial applications.

JP2025514353AActive Publication Date: 2025-05-02SHANXI CHINA CRYSTAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024563714
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-03-31
Publication Date
2025-05-02
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

The conventional VGF method for growing semi-insulating gallium arsenide (GaAs) crystals results in inconsistent carbon concentration and electrical properties due to slow oxygen release from graphite and quartz, leading to non-uniform resistivity and mobility.

Method used

A method involving a VGF single crystal furnace with graphite and quartz crucibles in different temperature zones, where the graphite is pretreated to remove moisture and the CO content is controlled through precise temperature management, ensuring uniform carbon doping and improved electrical properties.

Benefits of technology

The method achieves a resistivity range of 0.1×10^8 to 5×10^8 Ω·cm with a radial resistivity change of less than 8%, and uniform carbon and silicon concentrations, resulting in enhanced electrical properties and commercial viability of the GaAs crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514353000001_ABST
    Figure 2025514353000001_ABST
Patent Text Reader

Abstract

The present application relates to a semi-insulating gallium arsenide single crystal and its manufacturing method and growth device, the manufacturing method of which includes the steps of: putting a crystal raw material into a PBN crucible, moving it into a quartz crucible, placing graphite in a quartz cap, and then sealingly connecting it with the quartz crucible (S1); loading it into a VGF single crystal furnace after sealing and connecting it, and the quartz cap and the quartz crucible are in different temperature zones (S2); and raising the temperature of the temperature zone where the quartz crucible is located to the melting temperature, while simultaneously raising the temperature of the temperature zone where the quartz cap is located to 1000±50°C (S3). The present application discloses a semi-insulating gallium arsenide single crystal and a manufacturing method and growth apparatus thereof, which include steps S3, S4, S5, S6, and S7, in which the temperature zone where the quartz cap is located is controlled to drop to 1000°C±50°C, and the temperature is maintained, doped with the atmosphere, and the crystal is grown. The method of the present application can effectively improve the amount of carbon doping inside the gallium arsenide crystal and the uniformity of the electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE This application relates to the field of single crystal compounds, and in particular to semi-insulating gallium arsenide single crystals and methods and growth apparatus for their manufacture. [Background technology]

[0002] Gallium arsenide (GaAs) material is the most important material among the second generation new compound semiconductors following silicon single crystal. Due to its excellent performance, high electron mobility and photoelectric conversion efficiency, it is widely used in the fields of microelectronics and optoelectronics, especially in the commercialization process of 5G.

[0003] Resistivity and mobility are the main performance parameters of semi-insulating gallium arsenide (GaAs) crystals, and the carbon concentration in the crystal has an important influence on resistivity and mobility. In the growth of semi-insulating gallium arsenide crystals by the conventional VGF method, the amount of carbon doping is often controlled by the reaction between high-purity graphite and oxygen released from quartz (produced by the decomposition of quartz and boron oxide), or by the reaction between high-purity graphite and water (trace amounts of water adsorbed by graphite or quartz).

[0004] In the above VGF method, graphite and quartz slowly release oxygen at high temperatures, so the increase and diffusion of CO concentration in the atmosphere is very slow, so there is a gradient difference in the carbon content inside the gallium arsenide crystal, and the difference between the head and tail in the vertical direction inside the crystal is particularly significant. The final product has a resistivity of 10 7 ~10 8 The electrical properties vary from Ω·cm to Ω·cm and are poorly consistent, severely limiting their commercial use. Summary of the Invention [Problem to be solved by the invention]

[0005] In order to improve the uniformity of the carbon concentration in a gallium arsenide crystal and its performance such as resistivity, mobility, etc., the present application provides a semi-insulating gallium arsenide single crystal and its manufacturing method and growth apparatus. [Means for solving the problem]

[0006] In a first aspect, the present application provides a semi-insulating gallium arsenide single crystal, the semi-insulating gallium arsenide single crystal having a resistivity of 0.1×10 8 ~5×10 8 Ω cm, the change in radial resistivity is less than 8%, and the Si concentration is 1.14×10 13 ~4.5×10 15 Atoms cm -3 and the concentration of C is 6×10 15 ~2.0×10 16 Atoms cm -3 It is.

[0007] This semi-insulating gallium arsenide single crystal has excellent electrical properties such as resistivity and mobility, and the uniformity of its electrical performance is outstanding.

[0008] In a second aspect, the present application provides a method for producing a method of S1: placing GaAs polycrystals, a seed crystal, and boron oxide in a PBN crucible, moving the PBN crucible into a quartz crucible, placing graphite in a quartz cap, and hermetically connecting the quartz cap and the quartz crucible; S2, the quartz cap and the quartz crucible hermetically connected in step S1 are loaded into a VGF single crystal furnace, and the quartz cap and the quartz crucible are in different temperature zones; S3, which controls the temperature zone where the quartz crucible is located so as to increase the temperature to the melting temperature, and at the same time controls the temperature zone where the quartz cap is located so as to increase the temperature to 1000±50° C.; When the temperature zone where the quartz crucible is located reaches the melting temperature, the quartz crucible is melted by keeping the temperature, and the temperature zone where the quartz cap is located is controlled so that the temperature is increased to 1200±50°C and kept at that temperature for 4 to 50 hours (S4); After the melting is completed, the temperature zone where the quartz cap is located is controlled to drop to 1000°C ± 50°C, and the temperature is kept constant, and the atmosphere is doped to grow crystals (S5); S6 decreasing the temperature and discharging the material.

[0009] The above technical solution provides a new method for controlling the amount of carbon doping, by placing the quartz cap filled with graphite and the quartz crucible in different temperature zones, and controlling the temperature zone where the quartz cap is located to be at an appropriate temperature to promote the following reaction between graphite and quartz: JPEG2025514353000002.jpg639The CO generated by the reaction provides the main carbon source for atmosphere doping, realizing effective carbon doping of microwave crystals, and realizing the control of the carbon content in the atmosphere by controlling the chemical reaction process. Of course, there is also a small amount of CO generated in the atmosphere by the reaction of C with H2O or O2.

[0010] In controlling the above reaction, when the temperature of the temperature zone where graphite is present is ≦1000° C., the reaction between C and SiO2 does not proceed essentially, i.e., in steps S3 and S5, graphite does not substantially react with quartz to produce CO, and when the temperature of the temperature zone where graphite is present is ≧1200° C., the reaction between C and SiO2 continues, i.e., in step S4, CO continues to be produced. The reaction time length at temperatures ≧1200° C. should be controlled to ensure that the CO content is stable.

[0011] The main route by which C is doped into GaAs is 2Ga+CO→Ga2O+C. The above-mentioned chemical reaction occurs between the free Ga in the GaAs and the CO in the atmosphere, and C is introduced into the GaAs.

[0012] Meanwhile, in the general VGF process, the carbon source for the atmospheric doping is mainly obtained by the reaction of graphite with moisture and oxygen contained in the growth apparatus or the graphite itself, and the reaction formula is: C+H2O→CO+H2, 2C+O2→2CO, C++O2→CO2, The route by which C is doped into GaAs is as follows: 2Ga+CO→Ga2O+C, 4Ga+CO2→Ga2O3+3C, However, in a high-temperature environment, the oxygen release in the graphite and the growth device (quartz) is slow, so the carbon concentration in the crystal is not large and the distribution is not uniform, the resistivity of the crystal is low, and the difference in each part is large, and the application performance is poor. Meanwhile, in this application, the reaction rate between C and SiO2 can be controlled by the temperature and the contact area between graphite and quartz. Generally, the higher the temperature of the temperature zone where graphite is located, the more the reaction proceeds to the right and becomes more intense, the greater the CO content in the atmosphere, and the greater the carbon content in the corresponding crystal. At the same time, the larger the contact area between graphite and quartz, the greater the CO content in the atmosphere, and the greater the carbon content in the corresponding crystal. As a result, the CO content in the atmosphere is relatively easy to control, and the C concentration in the crystal is more uniform, which contributes to improving the uniformity of the resistivity and mobility inside the crystal.

[0013] Preferably, the graphite is pretreated prior to inserting the quartz cap, the pretreatment being to remove moisture.

[0014] In the above technical solution, the graphite is placed in a quartz container, sealed, and evacuated, and then the quartz container can be baked to remove moisture in the graphite as much as possible, reduce the influence of CO concentration in the space atmosphere caused by CO generated by the reaction of C and H2O, improve the accuracy of the carbon doping amount in the crystal, and ensure that the crystal has high resistivity and mobility. In this application, there is no special requirement for the baking temperature, and usually, baking at a temperature of 200±30°C can achieve both efficiency and energy consumption.

[0015] Preferably, the PBN crucible, quartz crucible, quartz cap and VGF single crystal furnace are pretreated as described above before use.

[0016] The PBN crucible, quartz crucible and quartz cap must be pre-treated before use, and the moisture and oxygen content of the materials and equipment used in crystal growth must be strictly controlled to obtain gallium arsenide crystals with high resistivity.

[0017] Preferably, the vacuum level of the vacuum pump is within a range of (1 to 9×10 -4 )~(1~9×10 -2 )Pa.

[0018] The above technical solution can control sufficient discharge of moisture in the graphite raw material at the above vacuum level, reduce the occurrence of side reactions between graphite and water, and ensure the controllability of the CO content in the air atmosphere. Generally, when the baking time is about 2 to 4 hours at the above vacuum level, the moisture can be effectively removed.

[0019] Preferably, in step S5, the crystal growth is performed under conditions of a cooling rate of 0.1 to 10° C. / h and a temperature gradient of 0.1 to 10° C. / cm.

[0020] The cooling rates and temperature gradients of the above techniques effectively ensure the growth of semi-insulating gallium arsenide crystals.

[0021] In a third aspect, the present application provides an apparatus for growing semi-insulating gallium arsenide single crystals, including a VGF single crystal furnace, a quartz crucible located in the VGF single crystal furnace, and a PBN crucible located in the quartz crucible, the opening of the quartz crucible is provided with a quartz cap covering it, the quartz cap includes a receiving groove for placing graphite, the VGF single crystal furnace is provided with a first temperature zone and a second temperature zone in its axial direction, the quartz cap is located in the first temperature zone, and the quartz crucible is located in the second temperature zone.

[0022] By using the above technical solution, during the crystal growth process, there is a large difference between the temperature field required for crystal growth and the reaction temperature of C and SiO2, so in this application, the quartz tube in which graphite is placed and the quartz crucible in which raw materials such as gallium arsenide are placed are placed in different temperature zones of the VGF single crystal furnace, and the temperature required in each temperature zone is controlled by different heat sources.

[0023] Preferably, the quartz cap is provided with a transition pipe at one end close to the quartz crucible, the transition pipe communicating with the receiving groove.

[0024] Since the reaction temperature of graphite is significantly different from the growth temperature in the quartz crucible, in order to reduce the temperature interference between the two temperature zones, a transition pipe is provided between the receiving groove and the quartz crucible to ensure the reaction between graphite and quartz and to accurately control the CO content in the atmosphere.

[0025] Preferably, the diameter of the transition pipe is less than the width of the receiving groove.

[0026] By using the above technical solution, the diameter of the transition pipe is small and the overall shape is elongated, which contributes to reducing the thermal convection between the containing groove and the quartz crucible and improving the control accuracy of the reaction temperature of the containing tank.

[0027] Preferably, the first temperature zone comprises a plurality of temperature zones arranged in the axial direction of the VGF single crystal furnace, and the second temperature zone comprises a plurality of temperature zones arranged in the axial direction of the VGF single crystal furnace.

[0028] By using the above technical solutions, in the improved VGF process of the present application, since a suitable temperature gradient is required for the growth of gallium arsenide crystals, the first temperature zone needs to be divided into multiple independent small temperature zones in the axial direction to form a suitable temperature field and ensure the growth of crystals; meanwhile, the reaction between graphite and SiO2 requires a temperature field distinct from the first temperature zone, and the second temperature zone is also divided into multiple small temperature zones to ensure that the reaction temperature can be accurately controlled.

[0029] In addition, in order to realize effective control of temperature, the distance between the current temperature zones is generally controlled to 8cm to 25cm. In this application, the first temperature zone is preferably divided into six small temperature zones, which are designated as Tz1 to Tz6, and the second temperature zone is preferably divided into three small temperature zones, which are designated as Tz7 to Tz9. Effect of the Invention

[0030] In summary, the present application has the following beneficial effects: 1. In this application, the C in the graphite reacts with the SiO2 in the quartz cap to produce CO, which provides the main carbon source for the atmospheric doping in the growth of gallium arsenide crystals, effectively controls the CO content in the atmosphere, and ensures the uniformity of the carbon doping amount inside the crystal, thereby obtaining gallium arsenide single crystals with higher resistivity.

[0031] 2. In this application, the graphite and the growth equipment are pretreated to sufficiently reduce their moisture content, thereby reducing the influence of CO generated by the reaction of graphite with water on the carbon concentration of the crystal, and ensuring high resistivity of the crystal.

[0032] 3. In this application, by setting Tz7 to Tz9 corresponding to the quartz cap, the reaction process between C and SiO2 in the quartz cap can be accurately controlled, and the uniformity of the carbon concentration in the crystal and the uniformity of its internal resistivity, mobility, and other performances can be ensured. [Brief description of the drawings]

[0033] [Figure 1] FIG. 1 is a schematic diagram of a growth apparatus in the first embodiment of the present application. [Diagram 2] FIG. 2 is a schematic diagram of a growth apparatus in Example 2 of the present application. [Diagram 3] FIG. 3 is a graph showing the test results of the element content of the semi-insulating gallium arsenide crystal in Example 1 of the present application. [Figure 4] FIG. 4 is a graph showing the test results of the element content of the semi-insulating gallium arsenide crystal in Example 1 of the present application. [Explanation of symbols]

[0034] 1 VGF single crystal furnace 2 Quartz crucible 3 Quartz Cap 31 Storage Groove 32 Transition Pipeline 4 PBN crucible 5. First Temperature Zone 6 Second Temperature Zone DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Manufacturing Example Preparation Example 1: Graphite pillars are obtained by pretreatment. The specific operation of the pretreatment is to place the graphite pillars in a quartz tube, place the quartz tube in an oven, connect it to a vacuum device and seal it, and then evacuate the quartz tube to a vacuum degree of 9×10 -4 Place the quartz tube in an oven and bake at 200 °C for 4 hours to obtain a pressure of 1 Pa.

[0036] Preparation Example 2: Graphite pillars are obtained by pretreatment. The specific operation of the pretreatment is to place the graphite pillars in a quartz tube, place the quartz tube in an oven, connect it to a vacuum device and seal it, and then evacuate the quartz tube to a vacuum degree of 1×10 -2 Place the quartz tube in an oven and bake at 220 °C for 2 hours to obtain a pH of 1.2.

[0037] Production Example 3: Graphite pillars. The difference from Production Example 1 is that the graphite pillars were not pretreated.

[0038] Working Example Example 1 The present application provides a method for producing semi-insulating gallium arsenide single crystals, in which a semi-insulating gallium arsenide single crystal growth apparatus is used to grow crystals by the VGF method, and referring to Fig. 1, the growth apparatus includes a VGF single crystal furnace 1, a quartz crucible 2 is loaded in the VGF single crystal furnace 1, a PBN crucible 4 is loaded in the quartz crucible 2, and a quartz cap 3 is placed on the opening of the quartz crucible 2. The quartz cap 3 includes a receiving groove 31 in its main body, and a transition pipe 32 communicating with the receiving groove 31 is provided at the bottom of the quartz cap 3, and the diameter of the transition pipe 32 is smaller than the width of the receiving groove 31.

[0039] The VGF single crystal furnace 1 includes a first temperature zone 5 provided for the quartz crucible 2 and a second temperature zone 6 provided for the quartz cap 3. Furthermore, the first temperature zone 5 includes Tz1 to Tz6, and the second temperature zone 6 includes Tz7 to Tz9, and Tz1 to Tz9 are provided in order from bottom to top in the axial direction of the VGF single crystal furnace 1, and the temperature of each temperature zone is controlled independently.

[0040] The manufacturing method includes the following steps.

[0041] S1: 10 kg of 7N GaAs polycrystals, a seed crystal, and 30 g of boron oxide are placed in a 4-inch PBN crucible 4, then the PBN crucible 4 is moved into the quartz crucible 2 to complete the filling, and further a graphite pillar (manufactured in Manufacturing Example 1) with a diameter of 50 mm and a thickness (length) of 20 mm is placed in the accommodation groove 31 in the quartz cap 3, and the circular bottom surface of the graphite pillar is brought into contact with the accommodation groove 31, and then the quartz cap 3 and the quartz crucible 2 are hermetically connected (welded).

[0042] S2: The quartz cap 3 and the quartz crucible 2 that are hermetically connected in step S1 are loaded into the VGF single crystal furnace 1, and the quartz cap 3 is located at Tz7 to Tz9 of the VGF single crystal furnace 1, and the quartz crucible 2 is located at Tz1 to Tz6 of the VGF single crystal furnace 1.

[0043] S3: Tz1 to Tz6 are controlled so as to increase in temperature up to 1238°C (melting temperature), while simultaneously controlling Tz7 to Tz9 so as to increase in temperature up to 1000±50°C.

[0044] S4: When Tz1 to Tz6 reach 1238°C (melting temperature), they are kept warm for 6 to 12 hours to melt, and at the same time, the temperatures of Tz7 to Tz9 are controlled to increase to 1200±50°C in 30 minutes, and kept warm for 10 hours.

[0045] S5: After the GaAs polycrystal is melted, the crystal is grown by using the VGF method, and the cooling rate of Tz1~Tz6 is 2~6℃ / h, the temperature gradient is 0.1~5℃ / cm. At the same time, the temperature zones Tz7~Tz9 are controlled to drop to 1000℃±50℃ in 1 hour, and kept warm to ensure that the graphite and quartz react with each other, and form a CO atmosphere with a stable content.

[0046] S6: The temperature is decreased and the material is discharged. When Tz1 to Tz6 are in the range of 1200 to 1238°C, the temperature decrease rate is 2±1°C / h, when they are in the range of 1000 to 1200°C, the temperature decrease rate is 5 to 15°C / h, when they are in the range of 50 to 1000°C, the temperature decrease rate is 30±10°C / h. During this process, Tz7 to Tz9 are gradually decreased to the discharge temperature, and finally a semi-insulating gallium arsenide crystal with a length of 200 mm is obtained.

[0047] According to the test method specified in SJ / T11488-2015, the resistivity and mobility of the above-produced crystal were tested, and the test results are shown below. JPEG2025514353000003.jpg47147

[0048] Radial resistance change rate within the crystal (difference from average resistance value) = (test point resistance value / average value of test sheet) x 100%

[0049] The crystal head-to-tail resistance ratio value: head average value / tail average value=0.97.

[0050] The test results of element content are shown in Figure 3.

[0051] As can be seen from FIG. 3, the Si content is 1.14×10 13 ~4.5×10 15 Atoms cm -3 and the C content is between 6×10 15 ~2.0×10 16 Atoms cm -3 It is between.

[0052] Example 2 The present application provides a method for producing semi-insulating gallium arsenide single crystals, in which a semi-insulating gallium arsenide single crystal growth apparatus is used to grow crystals by the VGF method, and referring to Fig. 2, the growth apparatus includes a VGF single crystal furnace 1, a quartz crucible 2 is loaded in the VGF single crystal furnace 1, a PBN crucible 4 is loaded in the quartz crucible 2, and a quartz cap 3 is placed on the opening of the quartz crucible 2. The quartz cap 3 includes a receiving groove 31 in its main body, and a transition pipe 32 communicating with the receiving groove 31 is provided at the bottom of the quartz cap 3, and the diameter of the transition pipe 32 is smaller than the width of the receiving groove 31.

[0053] The VGF single crystal furnace 1 includes a first temperature zone 5 provided for the quartz crucible 2 and a second temperature zone 6 provided for the quartz cap 3. Furthermore, the first temperature zone 5 includes Tz1 to Tz6, and the second temperature zone 6 includes Tz7 to Tz9, and Tz1 to Tz9 are provided in order from bottom to top in the axial direction of the VGF single crystal furnace 1, and the temperature of each temperature zone is controlled independently.

[0054] The manufacturing method includes the following steps. S1: 24 kg of 7 N GaAs polycrystals, a seed crystal, and 65 g of boron oxide are placed in a 6-inch PBN crucible 4, then the PBN crucible 4 is moved into the quartz crucible 2 to complete the filling, and a graphite pillar (manufactured in Manufacturing Example 2) with a diameter of 60 mm and a thickness (length) of 20 mm is placed in the accommodation groove 31 in the quartz cap 3, and the circular bottom surface of the graphite pillar is brought into contact with the accommodation groove 31, and then the quartz cap 3 and the quartz crucible 2 are hermetically connected.

[0055] S2: The quartz cap 3 and the quartz crucible 2 that are hermetically connected in step S1 are loaded into the VGF single crystal furnace 1, and the quartz cap 3 is located at Tz7 to Tz9 of the VGF single crystal furnace 1, and the quartz crucible 2 is located at Tz1 to Tz6 of the VGF single crystal furnace 1.

[0056] S3: Tz1 to Tz6 are controlled so as to increase in temperature up to 1238°C (melting temperature), while simultaneously controlling Tz7 to Tz9 so as to increase in temperature up to 1000±50°C.

[0057] S4: When Tz1 to Tz6 reach 1238°C (melting temperature), they are kept warm for 6 to 10 hours to melt, and at the same time, the temperatures of Tz7 to Tz9 are controlled to rise to 1200±50°C in 30 minutes, and kept warm for 50 hours.

[0058] S5: After the GaAs polycrystal is melted, the crystal is grown by using the VGF method. The cooling rate of Tz1~Tz6 is 5~10℃ / h, and the temperature gradient is 3~8℃ / cm. At the same time, the temperature of Tz7~Tz9 is controlled to drop to 1000℃±50℃ in 1 hour, and the temperature is kept warm to ensure that the graphite and quartz react with each other, and a CO atmosphere with a stable content is formed.

[0059] S6: The temperature is decreased and the material is discharged. When Tz1 to Tz6 are in the range of 1200 to 1238°C, the temperature decrease rate is 2±1°C / h, when they are in the range of 1000 to 1200°C, the temperature decrease rate is 5 to 15°C / h, when they are in the range of 50 to 1000°C, the temperature decrease rate is 30±10°C / h. During this process, Tz7 to Tz9 are gradually decreased to the discharge temperature, and finally a semi-insulating gallium arsenide crystal with a length of 200 mm is obtained.

[0060] According to the test method specified in SJ / T11488-2015, the resistivity and mobility of the above-produced crystal were tested, and the test results are shown below. JPEG2025514353000004.jpg70147

[0061] Radial resistance change rate in crystal = (test point resistance value / average value of test sheet) x 100%

[0062] The crystal head-to-tail resistance ratio value: head average value / tail average value=0.72.

[0063] The test results of element content are shown in Figure 4.

[0064] As can be seen from FIG. 4, the Si content is 1.14×10 13 ~4.5×10 15 Atoms cm -3 and the C content is between 6×10 15 ~2.0×10 16 Atoms cm -3 It is between.

[0065] Example 3 This application discloses a method for producing semi-insulating gallium arsenide single crystal, and the difference between this method and Example 1 is that the production process is as follows:

[0066] S1: 10 kg of 7N GaAs polycrystals, a seed crystal, and 30 g of boron oxide are placed in a 4-inch PBN crucible 4, then the PBN crucible 4 is moved into the quartz crucible 2 to complete the filling, and a graphite pillar (manufactured in Manufacturing Example 1) with a diameter of 50 mm and a thickness of 20 mm is placed in the accommodation groove 31 in the quartz cap 3, and the circular bottom surface of the graphite pillar is brought into contact with the accommodation groove 31, and then the quartz cap 3 and the quartz crucible 2 are hermetically connected.

[0067] S2: The quartz cap 3 and the quartz crucible 2 that are hermetically connected in step S1 are loaded into the VGF single crystal furnace 1, and the quartz cap 3 is located at Tz7 to Tz9 of the VGF single crystal furnace 1, and the quartz crucible 2 is located at Tz1 to Tz6 of the VGF single crystal furnace 1.

[0068] S3: Tz1 to Tz6 are controlled so as to increase in temperature up to 1238°C (melting temperature), while simultaneously controlling Tz7 to Tz9 so as to increase in temperature up to 1000±50°C.

[0069] S4: When Tz1 to Tz6 reach 1238°C (melting temperature), they are kept warm for 6 to 12 hours to melt, and at the same time, the temperatures of Tz7 to Tz9 are controlled to rise to 1200±50°C in 30 minutes, and kept warm for 4 hours.

[0070] S5: After the GaAs polycrystal is melted, the crystal is grown by using the VGF method, and the cooling rate of Tz1~Tz6 is 0.1~5℃ / h, the temperature gradient is 2~7℃ / cm. At the same time, the temperature of Tz7~Tz9 is controlled to drop to 1000℃±50℃ in 1 hour, and the temperature is kept warm to ensure that the graphite and quartz react with each other, and a CO atmosphere with a stable content is formed.

[0071] S6: The temperature is decreased and the material is discharged. When Tz1 to Tz6 are in the range of 1200 to 1238°C, the temperature decrease rate is 2±1°C / h, when they are in the range of 1000 to 1200°C, the temperature decrease rate is 5 to 15°C / h, when they are in the range of 50 to 1000°C, the temperature decrease rate is 30±10°C / h. During this process, Tz7 to Tz9 are gradually decreased to the discharge temperature, and finally a semi-insulating gallium arsenide crystal with a length of 200 mm is obtained.

[0072] According to the test method specified in SJ / T11488-2015, the resistivity and mobility of the above-produced crystal were tested, and the test results are shown below. JPEG2025514353000005.jpg47147

[0073] The crystal head-to-tail resistance ratio value: head average value / tail average value=0.65.

[0074] Example 4 This application discloses a method for producing a semi-insulating gallium arsenide single crystal, and the difference from Example 1 is that the graphite pillar produced in Example 3 is used in step S1.

[0075] The resistivity and mobility of the above-mentioned manufactured crystals were tested according to the test method specified in SJ / T11488-2015. The test results showed that the parameters of the same batch of crystals were low consistency due to the lack of graphite moisture treatment, and the resistivity of the crystals obtained under the same process environment was less than 1×10 8 Ω·cm is acceptable, or 5×10 8 Even if the crystal parameters are inappropriate and cannot be measured, a single crystal will have good consistency in the parameters, indicating the presence of a normal crystal.

[0076] Example 5: A method for producing semi-insulating gallium arsenide single crystal, which is different from Example 1 in that the production process is as follows.

[0077] S1: 10 kg of 7N GaAs polycrystals, a seed crystal, and 30 g of boron oxide are placed in a 4-inch PBN crucible 4, then the PBN crucible 4 is moved into the quartz crucible 2 to complete the filling, and further a graphite pillar (manufactured in Manufacturing Example 1) with a diameter of 30 mm and a thickness (length) of 20 mm is placed in the accommodation groove 31 in the quartz cap 3, and the circular bottom surface of the graphite pillar is brought into contact with the graphite groove 31, and then the quartz cap 3 and the quartz crucible 2 are hermetically connected.

[0078] S2: The quartz cap 3 and the quartz crucible 2 that are hermetically connected in step S1 are loaded into the VGF single crystal furnace 1, and the quartz cap 3 is located at Tz7 to Tz9 of the VGF single crystal furnace 1, and the quartz crucible 2 is located at Tz1 to Tz6 of the VGF single crystal furnace 1.

[0079] S3: Tz1 to Tz6 are controlled so as to increase in temperature up to 1238°C (melting temperature), while simultaneously controlling Tz7 to Tz9 so as to increase in temperature up to 1000±50°C. S4: When Tz1 to Tz6 reach 1238°C (melting temperature), they are kept warm for 6 to 12 hours to melt, and at the same time, the temperatures of Tz7 to Tz9 are controlled to increase to 1200±50°C in 30 minutes and kept warm for 6 hours.

[0080] S5: After the GaAs polycrystal is melted, the crystal is grown by using the VGF method, and the cooling rate of Tz1~Tz6 is 2~6℃ / h, the temperature gradient is 0.1~5℃ / cm. At the same time, the temperature of Tz7~Tz9 is controlled to drop to 1000℃±50℃ in 1 hour, and the temperature is kept warm to ensure that the graphite and quartz react with each other, and a CO atmosphere with a stable content is formed.

[0081] S6: The temperature is decreased and the material is discharged. When Tz1 to Tz6 are in the range of 1200 to 1238°C, the temperature decrease rate is 1 to 3°C / h, when they are in the range of 1000 to 1200°C, the temperature decrease rate is 5 to 15°C / h, when they are in the range of 50 to 1000°C, the temperature decrease rate is 20 to 40°C / h. During this process, Tz7 to Tz9 are gradually decreased to the discharge temperature, and finally, a semi-insulating gallium arsenide crystal with a length of 200 mm is obtained.

[0082] According to the test method specified in SJ / T11488-2015, the resistivity and mobility of the above-produced crystal were tested, and the test results are shown below. JPEG2025514353000006.jpg47147

[0083] The crystal head-to-tail resistance ratio value: head average value / tail average value=0.78.

[0084] Comparative Example Comparative Example 1 The present application provides a method for producing semi-insulating gallium arsenide single crystals, in which a semi-insulating gallium arsenide single crystal growth apparatus is used to grow crystals by the VGF method, the growth apparatus includes a VGF single crystal furnace 1, in which a quartz crucible 2 and a quartz cap 3 are loaded, the quartz cap 3 is provided with a receiving groove 31, and the height of the receiving groove 31 is smaller than the depth of the quartz cap 3.

[0085] In the VGF single crystal furnace 1, temperature zones Tz1 to Tz6 are provided in the axial direction, each of which is provided with an independent heat source, and the quartz crucible 2 and the quartz cap 3 are both in the range of Tz1 to Tz6.

[0086] The manufacturing method includes the following steps. S1: 10 kg of 7 N GaAs polycrystals, a seed crystal, and 30 g of boron oxide are placed in a 4-inch PBN crucible 4, and then the PBN crucible 4 is moved into the quartz crucible 2 to complete the filling. Furthermore, a graphite pillar with a diameter of 50 mm and a thickness of 20 mm is placed in the accommodation groove 31 in the quartz cap 3, and the quartz cap 3 and the quartz crucible 2 are hermetically connected.

[0087] S2: The quartz cap 3 and the quartz crucible 2 that have been hermetically connected in step S1 are loaded into the VGF single crystal furnace 1.

[0088] S3: Control Tz1 to Tz6 so that the temperatures are increased to 1238°C (melting temperature).

[0089] S4: When Tz1 to Tz6 reach 1238°C (melting temperature), keep them warm for 6 to 10 hours to melt.

[0090] S5: After the GaAs polycrystal is melted, the crystal is grown using the VGF method, and the cooling rate of Tz1 to Tz6 is 1 to 5 °C / h and the temperature gradient is 2 to 6 °C / cm.

[0091] S6: The temperature is decreased and the material is discharged, where when Tz1-Tz6 are in the range of 1200-1238°C, the temperature decrease rate is 2±1°C / h, when they are in the range of 1000-1200°C, the temperature decrease rate is 5-15°C / h, and when they are in the range of 50-1000°C, the temperature decrease rate is 30±10°C / h, and finally a semi-insulating gallium arsenide crystal with a length of 200 mm is obtained.

[0092] According to the test method specified in SJ / T11488-2015, the resistivity and mobility of the above-produced crystal were tested, and the test results are shown below. JPEG2025514353000007.jpg64147

[0093] As can be seen from the above table, the data of the crystal tail is the inverse type, which is a P-type semiconductor crystal, and the high resistance hole cannot be measured, showing 105.

[0094] Comparative Example 2 The present application provides a method for producing semi-insulating gallium arsenide single crystal, and the difference between this method and Comparative Example 1 is that crystal growth is performed using the growth apparatus for semi-insulating gallium arsenide single crystal in Example 1, and the temperatures Tz7 to Tz9 are controlled to always be within the range of 1200±50°C.

[0095] The specific manufacturing process is as follows. S1: 10 kg of 7N GaAs polycrystals, a seed crystal, and 30 g of boron oxide are placed in a 4-inch PBN crucible 4, then the PBN crucible 4 is moved into the quartz crucible 2 to complete the filling, and a graphite pillar (manufactured in Manufacturing Example 1) with a diameter of 50 mm and a thickness (length) of 20 mm is placed in the accommodation groove 31 in the quartz cap 3, and the circular bottom surface of the graphite pillar is brought into contact with the accommodation groove 31, and then the quartz cap 3 and the quartz crucible 2 are hermetically connected.

[0096] S2: The quartz cap 3 and the quartz crucible 2 that are hermetically connected in step S1 are loaded into the VGF single crystal furnace 1, and the quartz cap 3 is located at Tz7 to Tz9 of the VGF single crystal furnace 1, and the quartz crucible 2 is located at Tz1 to Tz6 of the VGF single crystal furnace 1.

[0097] S3: Tz1 to Tz6 are controlled so as to increase in temperature up to 1238°C (melting temperature), while at the same time, Tz7 to Tz9 are controlled so as to increase in temperature up to 1200±50°C.

[0098] S4: When Tz1 to Tz6 reach 1238°C (melting temperature), they are kept at that temperature for 8 hours to melt, and at the same time, the temperatures of Tz7 to Tz9 are controlled to increase to 1200±50°C.

[0099] S5: After the GaAs polycrystal is melted, the crystal is grown by using the VGF method, and the cooling rate of Tz1~Tz6 is 2~6℃ / h, the temperature gradient is 0.1~5℃ / cm. At the same time, the temperature of Tz7~Tz9 is controlled to be kept at 1200℃±50℃, to ensure that the graphite and quartz react with each other, and to form a CO atmosphere with a stable content.

[0100] S6: The temperature is decreased and the material is discharged. When Tz1 to Tz6 are in the range of 1200 to 1238°C, the temperature decrease rate is 2±1°C / h, when they are in the range of 1000 to 1200°C, the temperature decrease rate is 5 to 15°C / h, when they are in the range of 50 to 1000°C, the temperature decrease rate is 30±10°C / h. During this process, Tz7 to Tz9 are gradually decreased to the discharge temperature, and finally a semi-insulating gallium arsenide crystal with a length of 200 mm is obtained.

[0101] According to the test method specified in SJ / T11488-2015, the resistivity and mobility of the above-produced crystal were tested, and the test results are shown below. JPEG2025514353000008.jpg64147

[0102] As can be seen from the above table, the data of the crystal tail is the inverse type, which is a P-type semiconductor crystal, and the high resistance hole cannot be measured, showing 105.

[0103] Analysis of test results: (1) As can be seen from Examples 1-5 and Comparative Examples 1-2, in Examples 1-5, the quartz crucibles in which graphite and gallium arsenide crystals are grown are in different temperature zones, and the temperature of the temperature zone in which graphite is located is controlled to reach an appropriate reaction temperature to realize carbon doping of semi-insulating gallium arsenide, while in Comparative Example 1, the growth of semi-insulating gallium arsenide is performed using a general VGF method. The test results show that, compared with Comparative Example 1, the resistivity of the crystals obtained in Examples 1-5 is obviously more uniformly distributed, and the resistance ratio value of the crystal head to tail is smaller.

[0104] The reason for this is that in this application, the CO content in the space atmosphere is JPEG2025514353000009.jpg639 reaction, the higher the reaction temperature, the more the reaction moves to the right, the longer the reaction time, the higher the CO content in the atmosphere, and at the same time, the larger the contact area between graphite (C) and the quartz tube (SiO2), the higher the CO content. This reaction process is easy to control and can rapidly generate CO gas in the growth device, so that the CO content at each point in the growth device is relatively uniform, and further ensure the uniformity of the carbon doping amount in the gallium arsenide crystal. Meanwhile, in Comparative Example 1, the CO content in the atmosphere is mainly controlled by the reaction of graphite with water, oxygen released from the quartz cap (generating the quartz cap and boron oxide), or the reaction of graphite with water (generating graphite or quartz cap), etc. Due to the slow release rate of oxygen in a high temperature environment, the increase and diffusion of the CO content in the atmosphere is very slow, and the grown gallium arsenide crystal has low uniformity in the carbon content within it, and therefore its electrical properties are also different.

[0105] In Comparative Example 2, Tz7 to Tz9 are always at a high temperature of 1200±50°C, and the graphite and quartz are always in contact with each other. JPEG2025514353000010.jpg639As the reaction continues to run and CO is continuously produced, the carbon content of the crystal changes rapidly, causing large changes in the crystal parameters of over 8%, making it difficult to control the final resistivity and mobility of the product.

[0106] The specific examples are merely illustrative of the present application and do not limit the present application. After reading this specification, a person skilled in the art may make amendments to the present examples as necessary without making any creative contribution thereto, but as long as they are within the scope of the claims of this application, they shall be protected by the Patent Law.

Claims

1. A method for producing a semi-insulating gallium arsenide single crystal, comprising the steps of: S1: placing GaAs polycrystals, a seed crystal, and boron oxide in a PBN crucible, moving the PBN crucible into a quartz crucible, placing graphite in a quartz cap, and hermetically connecting the quartz cap and the quartz crucible; The quartz cap and the quartz crucible hermetically connected in step S1 are loaded into a VGF single crystal furnace, and the quartz cap and the quartz crucible are in different temperature zones S2; S3: controlling the temperature zone where the quartz crucible is located so as to increase the temperature to the melting temperature, and at the same time, controlling the temperature zone where the quartz cap is located so as to increase the temperature to 1000±50° C.; When the temperature zone where the quartz crucible is located reaches the melting temperature, the quartz crucible is melted by keeping the temperature, and the temperature zone where the quartz cap is located is controlled so that the temperature is increased to 1200±50° C. and kept at that temperature for 4 to 50 hours (S4); After the melting is completed, the temperature of the temperature zone where the quartz cap is located is controlled to drop to 1000° C.±50° C., and the temperature is kept constant, and the atmosphere is doped to grow a crystal (S5); S6 decreasing the temperature and discharging the material.

2. 2. The method for producing a semi-insulating gallium arsenide single crystal according to claim 1, further comprising the steps of: pretreating the graphite before inserting the quartz cap; and removing moisture from the graphite.

3. The method for producing semi-insulating gallium arsenide single crystals according to claim 2, characterized in that the PBN crucible (4), the quartz crucible (2), the quartz cap (3) and the VGF single crystal furnace (1) are subjected to the pretreatment before use.

4. The pretreatment includes a vacuum evacuation operation, and the absolute vacuum of the vacuum evacuation operation is (1 to 9×10 -4 ) ~ (1 ~ 9 x 10 -2 3. The method for producing a semi-insulating gallium arsenide single crystal according to claim 2, wherein the temperature is 1000° C. or more.

5. 2. The method for producing a semi-insulating gallium arsenide single crystal according to claim 1, wherein in step S5, the crystal growth is performed under conditions of a cooling rate of 0.1 to 10 ° C. / h and a temperature gradient of 0.1 to 10 ° C. / cm.

6. Using the manufacturing method, a semi-insulating gallium arsenide single crystal is obtained, and the resistivity of the semi-insulating gallium arsenide single crystal is 0.1×10 8 ~5×10 8 Ω cm, the change in radial resistivity is less than 8%, and the concentration of Si is 1.14×10 13 ~4.5 x 10 15 Atoms・cm -3 and the concentration of C is 6×10 15 ~2.0 x 10 16 Atoms・cm -3 2. The method for producing a semi-insulating gallium arsenide single crystal according to claim 1,

7. A semi-insulating gallium arsenide single crystal, The resistivity of the semi-insulating gallium arsenide single crystal is 0.1×10 8 ~5×10 8 Ω cm, the change in radial resistivity is less than 8%, and the concentration of Si is 1.14×10 13 ~4.5 x 10 15 Atoms・cm -3 and the concentration of C is 6×10 15 ~2.0 x 10 16 Atoms・cm -3 A semi-insulating gallium arsenide single crystal comprising:

8. 1. An apparatus for growing semi-insulating gallium arsenide single crystals, comprising:

7. A method for growing a semi-insulating gallium arsenide single crystal according to claim 1, or a method for producing a semi-insulating gallium arsenide single crystal according to claim 1, comprising: a VGF single crystal furnace (1); a quartz crucible (2) located in the VGF single crystal furnace (1); and a PBN crucible (4) provided in the quartz crucible (2). A quartz cap (3) is provided at the opening of the quartz crucible (2) to cover the opening, and a groove (31) for placing graphite is provided in the quartz cap (3). The VGF single crystal furnace (1) is provided with a first temperature zone (5) and a second temperature zone (6) in its axial direction, the quartz cap (3) is located in the second temperature zone (6), and the quartz crucible (2) is located in the first temperature zone (5).

9. 9. The apparatus for growing semi-insulating gallium arsenide single crystals according to claim 8, characterized in that the quartz cap (3) is provided with a transition tube (32) at one end close to the quartz crucible (2), the transition tube (32) communicating with the receiving groove (31).

10. 10. The apparatus for growing semi-insulating gallium arsenide single crystals according to claim 9, characterized in that the diameter of the transition tube (32) is smaller than the width of the receiving groove (31).

11. 9. The apparatus for growing semi-insulating gallium arsenide single crystals according to claim 8, characterized in that the first temperature zone (5) comprises a number of temperature zones arranged in the axial direction of the VGF single crystal furnace (1), and the second temperature zone (6) comprises a number of temperature zones arranged in the axial direction of the VGF single crystal furnace (1).

Citation Information

Patent Citations

  • Production of semi-insulative gaas single crystal

    JP1998167898A

  • Production of single crystal

    JP1999147785A

  • Method and Apparatus for Growing Semiconductor Crystals with Rigid Supports with Carbon Doping, Resistivity Control, Temperature Gradient Control

    JP2004534710A